Computer Programming with JAVA Java JumpStart: A Hands-on Training from Basics to Building Blocks - Gustian Rama Putra (Journal Social Science And Technology For Community Service, 2025)
This community service activity represents a collaborative effort between the College of Science and Technology, Guimaras State University, Philippines, and the Computer Science, Universitas Pakuan, Indonesia. The initiative was designed to support the Sustainable Development Goals (SDGs), specifically SDG 4: Quality Education, SDG 8: Decent Work and Economic Growth, SDG 9: Industry, Innovation, and Infrastructure, SDG 10: Reduced Inequalities, and SDG 17: Partnerships for the Goals. The primary objective of this program was to equip participants with foundational knowledge and practical skills in Java programming, fostering digital literacy, critical thinking, and problem-solving abilities essential for personal and professional growth in an increasingly technology-driven world. The expected outputs of the activity included equipping participants with a solid understanding of Java basics, enabling them to create simple Java applications independently, use integrated development environments (IDEs) like Eclipse or NetBeans effectively, and develop enhanced problem-solving skills through programming exercises. Participants were also introduced to foundational object-oriented programming concepts such as classes, objects, inheritance, and polymorphism, culminating in the creation of a functional project that integrates key Java programming concepts. Additionally, teachers gained the confidence and skills to incorporate Java programming into their classrooms or workshops, ensuring the program's long-term impact. The program demonstrated significant outcomes, as evidenced by the data in Table 3, where the average participant understanding exceeded 90%. This notable achievement underscores the success of the initiative in promoting knowledge transfer and skill development. Furthermore, it highlights the effective collaboration between Guimaras State University and Universitas Pakuan in advancing the tri dharma of higher education: teaching, research, and community service while delivering tangible benefits to the community. This success encourages both institutions to continue fostering partnerships that contribute to sustainable development and societal well-being.